Older adults display diminished error processing and response in a continuous tracking task. (16th June 2017) - Colino, Francisco L.; Howse, Harvey; Norton, Angela; Trska, Robert; Pluta, Anthony; Luehr, Stephen J. C.; Handy, Todd C.; Krigolson, Olave E.
Abstract: Advancing age is often accompanied by a decline in motor control that results in a decreased ability to successfully perform motor tasks. While there are multiple factors that contribute to age‐related deficits in motor control, one unexplored possibility is that age‐related deficits in our ability to evaluate motor output result in an increase in motor errors. In line with this, previous work from our laboratory demonstrated that motor errors evoked an error‐related negativity (ERN)—a component of the human ERP associated with error evaluation originating within the human medial‐frontal cortex. In the present study, we examined whether or not deficits in the medial‐frontal error evaluation system contribute to age‐related deficits in motor control. Two groups of participants (young, old) performed a computer‐based tracking task that paralleled driving while EEG data were recorded. Our results show that older adults committed more behavioral errors than young adults during performance of the tracking task. An analysis of our ERP data revealed that the amplitude of the ERN was reduced in older adults relative to young adults following motor errors. Our results make an important extension from previous work demonstrating age‐related reductions in the ERN during performance of cognitive tasks. Importantly, our results imply the possibility of understanding motor deficits in older age.